Introduction to AutoCAD 2012 : 2D and 3D design - Yarwood, Alf , 1917- (Routledge, 2011)
Alf Yarwood provides a practical, structured course of work matched to the latest release of AutoCAD. After introducing first principles and the creation of 2D technical drawings, he goes on to demonstrate the construction of 3D solid and surface model drawings and rendering